Prevalence and genetic characterization of Cryptosporidium species and Giardia duodenalis in lambs in Oromia Special Zone, Central Ethiopia. Issue 1 (December 2016) - Wegayehu, Teklu; Karim, Md; Li, Junqiang; Adamu, Haileeyesus; Erko, Berhanu; Zhang, Longxian; Tilahun, Getachew
Abstract Background Cryptosporidium andGiardia duodenalis are gastro-intestinal parasites that infect human and animals worldwide. Both parasites share a broad host range and are believed to be zoonosis. The aim of this study was to identify the species ofCryptosporidium and assemblages ofG. duodenalis in lambs and to elucidate their role in zoonotic transmission. Results A total of 389 fecal samples were collected from lambs and screened by microscopy and nested PCR targeting the small-subunit ribosomal RNA forCryptosporidium; and the small-subunit ribosomal RNA, triose phosphate isomerase, β-giardin, and glutamate dehydrogenase genes forG. duodenalis. The prevalence ofCryptosporidium andG. duodenalis was 2.1% (8/389) and 2.6% (10/389), respectively. The infection rate at the three study sites ranged from 1.3 to 3.1% forCryptosporidium and 1.6 to 3.9% forG. duodenalis ; but variation was not statistically significant (p  > 0.05). The finding also showed that there is no sex and age group associated difference in the occurrence ofCryptosporidium andG. duodenalis infections in lambs. Sequence analysis revealed that lambs were mono-infection withC. ubiquitum andG. duodenalis assemblage E. The analysis also indicated the presence of genetic variation within isolates of assemblage E; with 4 of them are novel genotypes at the small-subunit ribosomal RNA, β-giardin, and glutamate dehydrogenase genes. Conclusion The findings of the current study showed that lambs are capable of harboringC. ubiquitum andG. duodenalis assemblage E. This finding suggests that lambs might be sources for potentially zoonoticCryptosporidium species. This was first molecular study in lambs and contributes to a better understanding of the epidemiology ofCryptosporidium andG. duodenalis in central Ethiopia.